(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
Let A be a total abstract structure. We prove that if a set A |A|^n is admissible in every partial enumeration of A with semicomputable codomain, then A is semicomputable in A in the sense of Friedman - Shepherdson.